HOW DO BRAZILIANS PERCEIVE FOOD WASTE? - de Vargas Mores, Giana; Dal Moro, Leila; Casagranda, Yasmin Gomes; Dalla Corte, Vitor Francisco; Girardi, Gabriele (Revista Gestão Organizacional, 2021)
This research aims to identify the profile and factors associated with the perception of Brazilian consumers regarding food waste. The chosen technique was survey research, with the application of a structured online and self-administered questionnaire with 664 Brazilian consumers. Descriptive statistics were calculated and multivariate statistical techniques, such as factor analysis and multiple linear regression. Five factors have different affirmations on assessing and dealing with the food, besides the behavior concerning food and its respective waste. The factor regarding education was included in the survey, adapted from Richter (2017), which generated this factor. This is an additional result when applied to the Brazilian context. The waste is associated with behavioral factors. One of the main contributions was to present the use of metrics, which provide comparisons between different themes of food waste, providing proposals for the public policies and guidelines for minimizing this problem. The study helps with discussions based on a relevant topic for humanity and contemplating the UN SDGs through a national diagnosis. Academics, public, private, and non-profit organizations have increasingly brought the spotlight onto food waste. Implications of this study point to the need for effective policies turned to mitigate food waste.